(3CWHGb GdPgHs - (3GdCUagGfj , YHO GdeDef Hf gHI Gddg, TQa GdOjf,J (B600 (3g` s
(3ChdgG (B:s
(3oZrHQ edGHSge Te eYGWSge LQhG Ydi bdd GdNVQGA CPjGdkG s
(3BNQgG (B:s
"(3hEPG EHJdi EHQGgje QHg HcdeGJ aCJegf(B" (3Je GdcJGH s
(3Vef eLehY , JQJjHgG (B: (3ef U (B15 - (3U(B82s
(3GfXQ GdeNWhW eY MeGSI CHj JeGes
(3hJMJ cd SWQ aj GdeNWhW JQLeJg HGdaGQSjIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B170s
Keywords: (3GdCOHs